2016
DOI: 10.3389/fpsyg.2016.00849
|View full text |Cite
|
Sign up to set email alerts
|

Is Anorexia Nervosa a Disorder of the Self? A Psychological Approach

Abstract: The debate concerning the pathogenesis and the maintaining factors of eating disorders, anorexia nervosa in particular, is ongoing especially since therapeutic interventions do not result in satisfactory and enduring rates of remission. This paper presents a model for the pathogenesis of eating disorders, based on the hypothesis of a deficiency in the development of the self. We present the theory in light of new evidence concerning the role of attachment insecurity in the development and maintenance of eating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 80 publications
8
80
0
Order By: Relevance
“…This view is in agreement with a recent hypothesis that describe anorexia as a disturbance of the self (Amianto et al, 2016) specifically associated “with spatial functioning possibly related to experiencing one's own body as an integrated aspect of the self, and temporal functioning possibly related to integrating the self in a coherent narrative over time.” (p. 7). More, it is also in agreement with the free energy framework suggesting that pre-existing mental models shape current perception (Friston and Kiebel, 2009).…”
Section: Resultssupporting
confidence: 92%
“…This view is in agreement with a recent hypothesis that describe anorexia as a disturbance of the self (Amianto et al, 2016) specifically associated “with spatial functioning possibly related to experiencing one's own body as an integrated aspect of the self, and temporal functioning possibly related to integrating the self in a coherent narrative over time.” (p. 7). More, it is also in agreement with the free energy framework suggesting that pre-existing mental models shape current perception (Friston and Kiebel, 2009).…”
Section: Resultssupporting
confidence: 92%
“…According to literature studies, attachment styles might lay the groundwork for identity development and might represent an important psychopathological factor of resilience (Amianto, Northoff, Abbate Daga, Fassino, & Tasca, ; Mikulincer & Shaver, ). The prevalence of insecure attachment is high in adults with EDs, and several studies demonstrated connections between insecure attachment and ED psychopathology (Abbate‐Daga, Gramaglia, Amianto, Marzola, & Fassino, ; Tasca & Balfour, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these assessments, a combination of a categorical diagnosis and a dimensional description of the patient's personality and attachment functioning can be suggested in order to build a better understanding of the personal ED symptomology, appropriate treatments, and to promote good therapeutic alliance (Illing et al, 2010;Tasca et al, 2009b;. Since the degree of attachment security is associated with ED symptomology, an attachment-sensitive can be beneficial for certain ED patients (Amianto et al, 2016;.…”
Section: Conclusion and Treatment Implicationsmentioning
confidence: 99%
“…Attachment interventions in ED treatment should support four key areas (Amianto et al, 2016;Faber & Dubé , 2015;Keating et al, 2013;Kuipers et al, 2016;Maxwell et al, 2014;Tasca et al, 2009aTasca et al, , b, 2011Tasca et al, , 2013…”
Section: Conclusion and Treatment Implicationsmentioning
confidence: 99%